2020
DOI: 10.1159/000507194
|View full text |Cite
|
Sign up to set email alerts
|

Liver Embolisation for Patients with Neuroendocrine Neoplasms: Systematic Review

Abstract: Background: Liver embolisation is one of the treatment options available for patients diagnosed with neuro-endocrine neoplasms (NEN). It is still uncertain whether the benefits of the various types of embolisation treatments truly outweigh the complications in NENs. This systematic review assesses the available data relating to liver embolisation in patients with NENs. Methods: Eligible studies (identified using MED-LINE-PubMed) were those reporting data on NEN patients who had undergone any type of liver embo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 130 publications
(108 reference statements)
2
10
0
Order By: Relevance
“…Based on our findings, interferon-alpha seems to have a minor role in the management of SBNETs and to be rarely used in clinical practice. Liver embolization was a preferred treatment option for patients with functioning tumours, in keeping with data from recent systematic review and meta-analysis[ 17 ], which reported a pooled symptomatic response of 55.2%. Chemotherapy was mainly used as a rescue treatment when progression to other available treatments was shown, and was mainly suggested for patients with rapid progression.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Based on our findings, interferon-alpha seems to have a minor role in the management of SBNETs and to be rarely used in clinical practice. Liver embolization was a preferred treatment option for patients with functioning tumours, in keeping with data from recent systematic review and meta-analysis[ 17 ], which reported a pooled symptomatic response of 55.2%. Chemotherapy was mainly used as a rescue treatment when progression to other available treatments was shown, and was mainly suggested for patients with rapid progression.…”
Section: Discussionsupporting
confidence: 55%
“…However, the right choice for third-line treatment remains unclear and practice regarding the use of everolimus, chemotherapy and other therapy options is likely to vary significantly between different institutions. Such therapeutic options may include everolimus[ 16 ] (approved for patients with non-functioning SBNETs), liver embolization[ 17 ], chemotherapy (mainly alkylating-based or oxaliplatin-based and generally combined with fluoropyrimidine)[ 18 , 19 ] and interferon-alpha[ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radio-embolisation with intrahepatic infusion of 90 Ycoated resin or glass particles has shown promising results. In systematic reviews, there has not been shown any differences in effect between bland-chemo-and radioembolization of the liver [53]. Orthotopic liver transplantation is rarely indicated, but may be considered in carefully selected young patients without extrahepatic disease and with a Ki-67 index <10%.…”
Section: Management Of Net Liver Metastasesmentioning
confidence: 99%
“…The importance of neuroendocrine liver metastases (NELM) in the survival of patients with advanced panNENs is represented not only by the fact that presence of liver metastases is associated with worse survival [ 11 , 70 , 155 , 162 , 337 , 338 , 339 , 340 , 341 ], but also by a significant correlation between the higher tumor burden of NELM and worse outcomes with PRRT [ 59 , 62 , 186 , 213 ], SSA [ 173 , 174 , 177 , 179 , 225 ], liver-directed therapy [ 342 ], and chemotherapy [ 321 ] ( Table 5 ). Several studies have reported the efficacy of liver-directed therapies including TACE/TAE and radio-embolization using 90 Y-labeled microspheres (selective internal radiotherapy [SIRT]), in controlling focal progression of NELM [ 69 , 70 , 71 , 72 , 74 , 341 , 343 ], as well as in controlling symptoms due to the liver metastases or hormone excess state of a F-panNENs [ 9 , 39 , 70 , 71 , 74 , 341 , 344 ]. The mean overall ORR to radio-embolization in a review of 12 studies including >400 patients with unresectable NELM was 55% (range 12–89%) and stable disease in 32% (range 10–60%) [ 9 ].…”
Section: Predictive Factors For Response To Liver-directed Therapies ...mentioning
confidence: 99%
“…These results are increasingly supported by additional recent non-prospective studies [ 25 , 56 , 57 , 60 , 61 , 62 , 63 ]. Several studies have reported the anti-tumor efficacy of various chemotherapies [ 13 , 14 , 18 , 31 , 64 , 65 , 66 , 67 , 68 ], as well as liver-directed therapies including transarterial chemoembolization/embolization (TACE/TAE) or radio-embolization [ 14 , 18 , 31 , 69 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Introductionmentioning
confidence: 99%